Geographical socioeconomic inequalities in healthy life expectancy in Japan, 2010-2014: An ecological study. - Aoi Kataoka, MHSc; Keisuke Fukui, Ph.D; Tomoharu Sato, Ph.D; Hiroyuki Kikuchi, Ph.D; Shigeru Inoue, Ph.D; Naoki Kondo, Ph.D; Tomoki Nakaya, Ph.D; Yuri Ito, Ph.D (Elsevier, 2021)
ABSTRACTS: Background: Area differences in life expectancy (LE) and healthy life expectancy (HLE) in large geographical units have been monitored around the world. Area characteristics may be based on culture, history, socioeconomic status and discrimination in smaller geographical units, so it is important to consider these when looking at health inequality. We aimed to evaluate LE, HLE, and non-healthy life expectancy (NHLE) in 1707 municipalities using Areal Deprivation Index (ADI) in Japan for the first time. Methods: We calculated the observed LE, HLE, and NHLE using death, population, and Long-term care insurance data for 2010-2014 and applied the variance weighted least squares model to estimate LE, HLE, and NHLE by 100 percentiles using the standardized ADI. Findings: The estimated LE, HLE, and NHLE became lower as the deprivation index worsened: the differences between the most and least deprived areas for HLE were 2·49 years for LE and 2·32 years for HLE in males; 1·22 years for LE and 0·93 years for HLE in females. The observed LE and HLE in the most deprived areas were much lower than other areas. Interpretation: Using ADI has enabled us to see the disparity within municipalities precisely. LE and HLE outlier for the 100th percentile might be linked to historical areal deprivation and marginalization. Precise monitoring of socioeconomic status-based health inequalities could help manage these inequalities by identifying the groups most in need of intervention.